Environmental pollution and renewal energy consumption in Vietnam - Ngoc, Minh Ngo; Ngoc, Thuc Nguyen; Huu, Khanh Vo; Xuan, Giang Pham; Phuc, Chan Tran Hoa (Journal of Social Economics Research, 2024)
The purpose of this paper is to find out the perusable empirical evidence on the nexus between environmental pollution and various factors on renewable energy consumption in the case of Vietnam. In Vietnam, being aware of the potential and role of renewable energy in economic development as well as environmental protection, the government affirms that renewable energy development does not only focus on expanding the scale and increasing the proportion of renewable energy sources in the total primary energy supply, contributing to decreasing environmental pollution. This research delves into the application of the autoregressive distributed lag (ARDL) methodology to examine the effects of environmental pollution and various factors on renewable energy consumption in Vietnam from 1995 to 2019. The findings suggest that globalization and population growth have a positive impact on advancing renewable energy consumption, whereas financial development does not have a significant long-term effect. Specifically, the two variables mentioned contribute to the increase in renewable energy consumption. Furthermore, the study reveals that increasing CO2 emissions and financial development are associated with a decrease in renewable energy consumption. Consequently, the paper offers policy recommendations aimed at facilitating the transition to a renewable energy-based economy in Vietnam in the near future.